Sebuah Laporan Kasus: Kejang Demam Sederhana - Lifkha Afriyana; Inggrit Anggraini; Supriadi Supriadi; Siska Silviana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Febrile seizures are seizures that occur in children aged 6 months to 5 years who experience an increase in body temperature (temperature above 38.0C, by any temperature measurement method) which is not caused by an intracranial process. (1) Febrile seizures are divided into febrile seizures simple and complex. Simple febrile seizures are common at onset, last less than 15 minutes, and do not occur more than once in 24 hours. Complex seizures are longer lasting, have focal symptoms, and can recur within 24 hours. We report a case of sudden high fever since 1 day ago accompanied by with seizures lasting 1 day for < 5 minutes. During a seizure, the patient is unconscious with his eyes upturned, his whole-body stiff. Denied cough complaints. Nausea and vomiting denied. Defecate once a day, the consistency is soft and yellowish in color. Urination no complaints.